(untitled) (Research, Society and Development, 2022)
Studies documenting the impacts caused by plastic pollution in the ocean increase every year. Many, however, do not describe or reveal little about the occurrence and impacts on coastal and marine ecosystems, being even more reduced when facing the southern Atlantic region and marine fauna. This fact reveals challenges for researchers in understanding the damage caused to ecosystems, even more when added to other responses that these ecosystems can manifest, such as anthropogenic climate change, enhancing a serious global problem that may be being underestimated, showing gaps. Thus, our aims in this research were to identify the main impacts of plastic on the Brazilian marine fauna and where they occurred, for that, a critical bibliographic review was carried out on the occurrence and impacts already raised by pollution from plastic waste in different marine coastal ecosystems of the Brazilian coast. Thirty-six articles were selected that pointed out debris from recreational activities, fishing, and urban activities. The impacts covered seabirds, cetaceans, pinnipeds, fish, sea turtles and marine invertebrates. The main impacts to marine communities were through the ingestion of plastic debris, in addition to direct pollution of coastal environments. The results contribute to a better understanding of the effects on Brazilian coastal and marine areas. Finally, the importance of expanding studies aimed at quantification, monitoring and analysis of these impacts on the coastal and marine environment is reinforced.